Why Managers and Companies Take Risks - Coleman, Les (Contributions to Management Science, 2006)
The book answers a simple question: when managers and companies face a decision with two outcomes that are safe and risky, what leads them to choose the risky alternative? The answer starts with a detailed review of the theory behind risk and decision making by managers. The book then gathers real-world evidence using two surveys of senior managers and directors to analyse why they take risks, and how companies control risks. Integrating theory and evidence the book develops a model of risk taking that draws from academic thinking across multiple disciplines and the actual practice of experienced managers. The last section of the book discusses how managers can apply its findings to dialling up the required level of risk inside their firm.